The Effect of CSR Activities on Purchase Intention: The Mediating Role of Brand Image and Corporate Image on UNIQLO - Rizki Juwita Sari; Anton Agus Setyawan (International Journal of Management Science and Information Technology, 2025)
This study aims to explore the influence of corporate social responsibility (CSR) on consumer purchase intention, with corporate image and brand image as mediating variables, in the context of a multi-brand fashion company. The study utilized a quantitative approach with a correlational design, involving 140 respondents collected through an online survey using a Likert scale. Data analysis was conducted using Smart PLS 3.0 software. The results showed that CSR has a positive and significant influence on purchase intention, corporate image, and brand image. In addition, brand image also has a positive influence on purchase intention. However, corporate image did not show a significant effect in mediating the relationship between CSR and purchase intention, while brand image showed significant mediation. The validity and reliability of the data have been tested using the Confirmatory Factor Analysis method, with the results showing that all indicators are valid and reliable. This study confirms the importance of CSR as a strategy that strengthens corporate and brand image, while driving consumer purchase intention. Practical implications include the importance of fashion companies to design an integrated CSR strategy to increase competitiveness in the market. This research also recommends further studies to explore the mediation mechanism and expand the sample to other industries for generalization of the findings.